DEAD-Box RNA Helicase 42 Plays a Critical Role in Pre-mRNA Splicing under Cold Stress. Issue 1 (21st November 2019) - Lu, Chung-An; Huang, Chun-Kai; Huang, Wen-Shan; Huang, Tian-Sheng; Liu, Hsin-Yi; Chen, Yu-Fu
Abstract : A DEAD-box RNA helicase, OsRH42, plays an essential role in ensuring accurate pre-mRNA splicing to support normal rice plant growth under low ambient temperature. Abstract: Low temperature is an important environmental stress that adversely affects rice ( Oryza sativa ) growth and productivity. Splicing of pre-mRNA is a crucial posttranscriptional regulatory step in gene expression in plants and is sensitive to temperature. DEAD-box RNA helicases belong to an RNA helicase family involved in the rearrangement of ribonucleoprotein complexes and the modification of RNA structure and are therefore involved in all aspects of RNA metabolism. In this study, we demonstrate that the rate of pre-mRNA splicing is reduced in rice at low temperatures and that the DEAD-box RNA Helicase42 (OsRH42) is necessary to support effective splicing of pre-mRNA during mRNA maturation at low temperatures. OsRH42 expression is tightly coupled to temperature fluctuation, and OsRH42 is localized in the splicing speckles and interacts directly with U2 small nuclear RNA. Retarded pre-mRNA splicing and plant growth defects were exhibited by OsRH42 -knockdown transgenic lines at low temperatures, thus indicating that OsRH42 performs an essential role in ensuring accurate pre-mRNA splicing and normal plant growth under low ambient temperature. Unexpectedly, our results show that OsRH42 overexpression significantly disrupts the pre-mRNA splicing pathway, causing retarded plant growth and reducing plant cold tolerance. Combined, these results indicate that accurate control of OsRH42 homeostasis is essential for rice plants to respond to changes in ambient temperature. In addition, our study presents the molecular mechanism of DEAD-box RNA helicase function in pre-mRNA splicing, which is required for adaptation to cold stress in rice.